2018
DOI: 10.1002/pssr.201800053
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Carrier Concentration of NaF‐Treated CIGS Solar Cells Using Heat–Light Soaking and Subsequent Heating

Abstract: The combined effect of the heat–light soaking (HLS) and subsequent heat‐soaking (HS) processes is investigated on NaF‐free and NaF‐treated CIGS solar cells with CdS buffer layer. The HLS treatment improves cell efficiency slightly with increased open‐circuit voltage for NaF‐treated CIGS solar cells, whereas the cell efficiency deteriorates for NaF‐free CIGS solar cells. The different behaviors between both types of solar cells may be due to a Na‐containing new layer, which is formed at the CIGS surface region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…W190113). HLS treatment increased the V OC and carrier concentration ( N CV ) and reduced J SC, whereas the HS treatment yielded opposite results similar to the previous reports on alkali‐treated samples . The change in the width of the space charge region (SCR) was consistent to the change in N CV .…”
supporting
confidence: 84%
See 3 more Smart Citations
“…W190113). HLS treatment increased the V OC and carrier concentration ( N CV ) and reduced J SC, whereas the HS treatment yielded opposite results similar to the previous reports on alkali‐treated samples . The change in the width of the space charge region (SCR) was consistent to the change in N CV .…”
supporting
confidence: 84%
“…A recent report suggested that the carrier collection efficiency in the solar cell after HLS also depends on the presence of alkali metals near the Mo back contact . However, through the controlled HLS followed by HS treatment, the improvement in device performance can be realized . In addition, as shown in Figure , a reversible change in FF occurred due to HLS and HS treatments, which may be related to the defect states at the interface .…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The HLS had a beneficial effect on the KF‐treated CIGS solar cells by improving the open‐circuit voltage ( V OC ) and fill factor (FF) . A similar effect was observed for sodium fluoride (NaF)‐treated and cesium fluoride (CsF)‐treated CIGS solar cells . The improved V OC was attributed to a significantly increased net carrier concentration ( N CV ), rather than to change in the atomic concentrations of Cd, S, and O in the chemical bath deposition (CBD) cadmium sulfide (CdS) buffer layer.…”
Section: Introductionmentioning
confidence: 71%